PENGUASAAN HARTA WARISAN OLEH SEBAGIAN AHLI WARIS DI DESA ALUE BARO KECAMATAN MEUKEK ACEH SELATAN MENURUT PERSPEKTIF KOMPILASI HUKUM ISLAM - Fauzi, Fakhrul; Moulia, Nouvan (Jurist Argumentum: Pemikiran Intelektual Hukum, 2025)
In Alue Baro village, Meukek subdistrict, South Aceh Regency, a case of inheritance issues was found, where some heirs unilaterally controlled the inheritance left by their parents and did not give shares to other heirs. In this case, the position is occupied by a substitute heir, who is the son of the heir who should have received the inheritance from the testator. His father's position to receive the inheritance was transferred to the testator's grandson because the original heir had passed away before the testator. This substitute heir is often referred to as "Anak patah titi" (broken bridge child). In this case, the distribution of inheritance was carried out according to customary law, so the substitute heir was not given their rights because they were considered to have severed ties with the testator ("Patah titi"). This research uses an empirical juridical research method. Primary data was collected through direct interviews in the field, while secondary data was obtained through literature review. This research aims to identify and explain two key aspects: first, the reasons behind the unilateral control of inheritance by some heirs while denying the substitute heir's rights. Second, it examines the perspective of the Compilation of Islamic Law (KHI) on this practice. The research findings indicate that the actions of the heirs who unilaterally control the inheritance and do not give it to the testator's grandchild as a substitute heir in Alue Baro village, Meukek subdistrict, South Aceh, are based on the assumption that the grandchild is not entitled to the inheritance from the testator because their father, as the primary heir, had passed away earlier. This practice refers to local customary law that recognizes the "Patah titi" law in inheritance matters. According to the perspective of the Compilation of Islamic Law (KHI), which applies to muslim communities in Indonesia, the act of unilaterally controlling inheritance by heirs as occurred in Alue Baro Village is contrary to Article 185 of the KHI. The KHI grants substitute heirs the right to receive inheritance from the testator as long as they meet the requirements. Furthermore, the inheritance share received by the substitute heir is equal to the right that should have been received by the person they replaced.